Guru Granth Sahib: social concerns - Sagoo, Harbans Kaur (Manpreet Prakashan, 2013)
Papers presented at the National Seminar on 'Guru Grantha Sahib : Social Concerns' organized by Sri Guru Nanak Dev Khalsa College during 19-20 April 2012